Gangguan Fungsi Penghidu dan Pemeriksaannya - Effy Huriyati; Tuti Nelvia (Jurnal Kesehatan Andalas, 2014)
AbstrakLatar belakang: Fungsi penghidu pada manusia memegang peranan penting. Gangguan penghidu dapat mempengaruhi keselamatan dan kualitas hidup seseorang. Tujuan: Untuk mengetahui jenis gangguan penghidu, penyebab gangguan penghidu, dan pemeriksaannya. Tinjauan Pustaka: Gangguan penghidu dapat berupa anosmia yaitu hilangnya kemampuan penghidu, atau hiposmia yaitu berkurangnya kemampuan penghidu. Gangguan penghidu disebabkan gangguan konduksi, gangguan sensoria dan gangguan neural. Penyakit tersering penyebab gangguan penghidu yaitu rinosinusitis kronis, rinitis alergi, infeksi saluran nafas atas dan trauma kepala. Ada beberapa modalitas pemeriksaan kemosensoris fungsi penghidu diantaranya Tes “Sniffin sticks”. Dengan tes „Sniffin sticks” dapat diketahui ambang penghidu, diskriminasi penghidu dan identifikasi penghidu seseorang. Kesimpulan: Gangguan penghidu memerlukan perhatian khusus. Diantara beberapa modalitas pemeriksaan kemosensoris penghidu, tes “Sniffin sticks” mempunyai beberapa kelebihan.Kata kunci: Gangguan penghidu, anosmia, hiposmia, tes “Sniffin sticks”.AbstractBackground: Olfactory function in humans plays an important role. Olfactory disorders can affect the safety and quality of life. Objective: To determine the type of olfactory disorder, the causes of olfactory disorders, and the examination. Literature Review: Olfactory disorder can be not smell anything or anosmia, and reduced of smell or hyposmia. Olfactory disorders caused by conduction disturbances, neural disturbances and sensoris disturbances. Disease that often causes disturbances of olfactory function is, chronic rhinosinusitis, allergic rhinitis, upper respiratory tract infections and head trauma. There are several modalities to examine chemosensoris smelling function, one of them is “Sniffin sticks” test. This test can examine threshold, discrimination, and identification of smelling. Conclusions: Impaired smelling require special attention. Between some modalities to examine chemosensors smelling function, “Sniffin sticks” test has several advantages.Keywords: Olfactory disorders, anosmia, hyposmia, “Sniffin sticks” test.